Cognitive strategies for developing students’ reading comprehension skills using short stories - Rodríguez Sua, Martha (Revista de Estudios y Experiencias en Educación, 2021)
This paper highlights the importance of implementing cognitive strategies to improve reading comprehension skills in a second language. The study was carried out at Capellania public school located in Cajica, Cundinamarca, Colombia. An initial needs analysis indicated that participants did not enjoy reading due to a lack of knowledge on reading strategies. Therefore, the aim of this study was to determine how five cognitive reading strategies (CRSs) could improve the reading comprehension of forty ninth-grade students using short stories. The five cognitive strategies selected were predicting, asking questions before reading, visualizing while reading, summarizing the story by using graphic organizers, and answering reading comprehension questions after reading. A student blog, two questionnaires and class artifacts collected in a portfolio constituted the data collection methods. Data analysis included participants’ insights into the usefulness of the strategies. The findings revealed that the use of cognitive strategies facilitated comprehension of a text; giving readers the opportunity to activate their schemata, to understand the main ideas and to understand new vocabulary. Moreover, participants were able to construct meaning from the text, identify a purpose for reading and, therefore; increase their motivation to read. Additionally, the results of this study might provide ideas for other English or foreign language teachers interested in improving their students’ reading comprehension skills.